2021
DOI: 10.21203/rs.3.rs-150089/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing CPT symmetry in ortho-positronium decays with positronium annihilation tomography

Abstract: Charged lepton system symmetry under combined charge, parity, and time-reversal transformation (CPT) remains scarcely tested. Despite stringent quantum-electrodynamic limits, discrepancies in predictions for the electron–positron bound state (positronium atom) motivate further investigation, including fundamental symmetry tests. While CPT noninvariance effects could be manifested in non-vanishing angular correlations between final-state photons and spin of annihilating positronium, measurements were previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In this opinion article, we discussed the current state of development of newly invented positronium imaging requiring high sensitivity and high-time-resolution multi-photon PET systems [1][2][3][4][5][6][7]. By reviewing the latest advances in the development of total-body and multi-photon PET systems, we have shown that the current PET technology is ready for effective positronium imaging in clinics with the spatial resolution comparable to that of the current PET images.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this opinion article, we discussed the current state of development of newly invented positronium imaging requiring high sensitivity and high-time-resolution multi-photon PET systems [1][2][3][4][5][6][7]. By reviewing the latest advances in the development of total-body and multi-photon PET systems, we have shown that the current PET technology is ready for effective positronium imaging in clinics with the spatial resolution comparable to that of the current PET images.…”
Section: Discussionmentioning
confidence: 99%
“…The first positronium images have recently been demonstrated using the J-PET multi-photon scanner prototype [2,7]. J-PET tomograph was enabled to reconstruct positronium images for both three-photon annihilations [7] and two-photon pick-off annihilations of ortho-positronium [2], showing that both positronium lifetime imaging and imaging of the three-photon to two-photon rate ratios are feasible. Figure 1C compares the sensitivity of two-photon positronium imaging with standard two-photon PET imaging.…”
Section: Positronium Imaging With Multiphoton Positron Emission Tomog...mentioning
confidence: 99%
See 2 more Smart Citations